Ex-bolsistas Capes de doutorado pleno no país e exterior: um estudo comparado no âmbito das ciências biológicas II - Jesus, Sandra Lopes Hugo de (2011)
Over the last few years, numerous studies and discussions have taken place regarding the results achieved by doctorates with education completed in Brazil and abroad, and they have raised questions about the programs contributions to the scientific, technical, cultural, and innovation in the area of the Biological Sciences II discipline. Primarily, the studies main purpose was to verify quantitatively the data referring to the scientific productivity of the participants of the Capes PhD programs in Brazil and overseas. The data was compiled using their professional experience, completed academic supervisions, and published articles. The quantitative data analysis, which included a sample of 37 former fellows in each modality, showed no significant difference between the two programs. There was a predisposition of the Brazilians students to publish a greater number of articles. On average, they had published 1.29 more articles, when compared to the students abroad. There were 808 articles published by 36 the participants in the country; versus 517 published article by 24 overseas students. One scholarship recipient in Brazil did not present results regarding the scientific production. As for the participants abroad that number was 13. The number of participants that were working in this particular field of study was also higher for those who held a doctorate in Brazil, with 31 researchers, compared to 23 of the total number of students who did their PhD studies in a foreign country. With respect to academic supervisions, students who studied abroad supervised 91 students, while students, whose studies were held in Brazil, supervised 82 students on average. Some of the participants that held their PhD outside of Brazil went to universities with an aggregated institutio nal prestige that was deemed lower when compared to the Brazilian universities. It was concluded that, in the case of Biological Sciences II, Capes could improve its selective process for those seeking a full PhD scholarship outside of the country by establishing a more stringent selection process. The objective would be to produce a more effective process that would benefit both the students and CAPES. This improved process could facilitate the re- integration back into the academic life as well as assist the scientific productivity of the students after they have finished their studies abroad.